How to Promote Medical Graduates to Work in Rural Medical Institutions - Guangrong Wu (Forest Chemicals Review, 1970)
The number of medical graduates is more and more. Two questions are raised. One is these graduates could not find fit jobs in big cities, the other is short of medical and health talents in rural areas. How to solve the two questions, it is important to our healthy development. First, the paper investigated the reason of these difficulties and analyzed these government made some plans about raising courage graduates to support the development of the western regions.  Second, the paper thought that there should be set the related psychological courses in universities. At last, the paper suggests that our national and regional governments should provide some attractive policies to guide medical students to volunteer to participate in “New rural construction”, such as high salary, better material benefits and children’s education priority.